Platelet transfusion does not improve outcomes in patients with brain injury on antiplatelet therapy. (23rd February 2018) - Holzmacher, Jeremy L; Reynolds, Cassandra; Patel, Mayur; Maluso, Patrick; Holland, Seth; Gamsky, Nathaniel; Moore, Henry; Acquista, Elizabeth; Carrick, Matthew; Amdur, Richard; Hancock, Heather; Metzler, Michael; et al.
ABSTRACT: Introduction : Platelet dysfunction following traumatic brain injury (TBI) is associated with worse outcomes. The efficacy of platelet transfusion to reverse antiplatelet medication (APM) remains unknown. Thrombelastography platelet mapping (TEG-PM) assesses platelet function. We hypothesize that platelet transfusion can reverse the effects of APM but does not improve outcomes following TBI. Methods : An observational study at six US trauma centres was performed. Adult patients on APM with CT evident TBI after blunt injury were enrolled. Demographics, brain CT and TEG-PM results before/after platelet transfusion, length of stay (LOS), and injury severity score (ISS) were abstracted. Results : Sixty six patients were enrolled (89% aspirin, 50% clopidogrel, 23% dual APM) with 23 patients undergoing platelet transfusion. Transfused patients had significantly higher ISS and admission CT scores. Platelet transfusion significantly reduced platelet inhibition due to aspirin (76.0 ± 30.2% to 52.7 ± 31.5%, p  < 0.01), but had a non-significant impact on clopidogrel-associated inhibition ( p  = 0.07). Platelet transfusion was associated with longer length of stay (7.8 vs. 3.5 days, p  < 0.01), but there were no differences in mortality. Conclusion : Platelet transfusion significantly decreases platelet inhibition due to aspirin but is not associated with change in outcomes in patients on APM following TBI.